##### Using Conjugate Roots Theorem, factor the polynomial function completely

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet \$5

f(x)=x^6-73x^4-657x^2+729

Apr 11th, 2015

x^6−73x^4−657x^2+729=(x−1)(x+1)(x−9)(x^2+9)(x+9).......................

Apr 11th, 2015

the roots of the polynomial are,

x1=1

x2=−1

x3=9

x4=−9

x5=3i

x6=−3i

3i and -3i are complex roots , all the others are real roots

Apr 11th, 2015

This is the exact same answer I come up with and the computer is saying its not completely factored.

Apr 11th, 2015

x^6−73x^4−657x^2+729=(x−1)(x+1)(x−9)(x^2+9)(x+9)

this is equal to,

=(x−1)(x+1)(x−9) (x+3i)(x-3i)(x+9)...................

this is factorized completely......

here there are 6 roots because degree is 6

here (x+3i)(x-3i) forms the conjugate roots....

Apr 11th, 2015

Apr 11th, 2015

okay thank you

Apr 11th, 2015

WELCOME....

HOPE YOU UNDERSTOOD..............THANK YOU

Apr 11th, 2015

...
Apr 11th, 2015
...
Apr 11th, 2015
Oct 20th, 2017
check_circle
check_circle
check_circle

Secure Information

Content will be erased after question is completed.

check_circle